THE EFFECT OF REGIONAL TAXES ON BANDUNG CITY ORIGINAL REVENUE DURING THE COVID-19 PANDEMIC - Asep Effendi (Jurnal Info Sains : Informatika dan Sains, 2022)
One of the factors that support the progress of a region is the availability of adequate finance, including Regional Original Income. Regional Original Income comes from several sources, including Regional Taxes. Regional Taxes provide a relatively large contribution to Regional Original Income. Nonetheless, the COVID-19 pandemic has had a substantial influence on the contribution to PAD from municipal taxes. This study attempts to assess the simultaneous and partial impact of the Covid-19 epidemic on Bandung City's Original Revenue (PAD). The Bandung City Tax Office conducts quantitative research employing descriptive and verification techniques. The data were then evaluated using the application EViews-12. All of the components of local taxes examined in this study had a substantial effect in the direction of a positive association with the Regional Original Income of the city of Bandung, as indicated by the results. Additionally, partially only restaurant tax has a significant effect on the direction of a negative relationship between Bandung City Original Revenue and Original Local Revenue, whereas other local tax components have no significant effect on the direction of a positive relationship between Original Local Revenue and Bandung City Original Revenue